2020
DOI: 10.1007/s10479-020-03834-y
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility: How much is enough? A higher dimension perspective of the relationship between financial and social performance

Abstract: We investigate the nature of the relationship between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP) by examining how it changes across a third dimension that accounts for firm-specific factors. We propose a semi-latent specification of an endogenous control variable, which can, for the first time, explicitly identify, for each individual firm, the threshold level where the marginal impact of CSR on CFP turns positive. We provide empirical evidence that this threshold depends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…The return on equity (ROE) was deemed the proxy for the CFP, referring to the percentage rate of net profit divided by net assets. It is an effective measure of the firm's ability to maximize profit from a capital investment [66] and sample firms' ROE mainly ranges from 0-20%. Independent variable.…”
Section: Variablesmentioning
confidence: 99%
“…The return on equity (ROE) was deemed the proxy for the CFP, referring to the percentage rate of net profit divided by net assets. It is an effective measure of the firm's ability to maximize profit from a capital investment [66] and sample firms' ROE mainly ranges from 0-20%. Independent variable.…”
Section: Variablesmentioning
confidence: 99%
“…Theoretically, token and critical mass theories (Kanter 1977a(Kanter , 1977b posit that women's ability to influence any firm's outcome (e.g., job satisfaction, turnover, and FP) depends fundamentally on their number, that is, high (low) female representation is likely to have a positive (negative) effect on outcomes. Likewise, many authors have shown the nonlinearity of factors influencing performance, whether financial or social in nature (Kalaitzoglou et al 2020). Many empirical studies have confirmed this theoretical viewpoint.…”
Section: Introductionmentioning
confidence: 85%
“…Until now, most scholars have focused on the link between ESG scores and corporate financial performance (e.g., Friede et al (2015); Cornett et al (2016); Henke (2016); El Ghoul et al (2017); Hou et al (2019); Behl et al (2021); Kalaitzoglou et al (2021)). Then recently, some studies have started to analyze the link between ESG scores and risk measures (e.g., Shafer et al (2020); Bax et al (2021); Giese et al (2021); Maiti (2021)).…”
Section: Literature Reviewmentioning
confidence: 99%